2017
DOI: 10.1007/s11655-016-2642-7
|View full text |Cite
|
Sign up to set email alerts
|

A general description for Chinese medicine in treating premature ovarian failure

Abstract: Premature ovarian failure (POF) is a kind of gynecological disease that causes amenorrhea, infertility, menopause and urogenital symptoms. Currently hormone replacement therapy (HRT) is the most popular choice for women with POF to get rid of menopausal syndrome. However, as the popularization of Chinese herbs made Chinese medicine (CM) shine new lights, physicians are able to treat POF with both meno-herbs and integrated therapy. HRT has its own indications and contraindications. For example, unexplained vagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Genetic [ 7 , 8 ], immunological [ 9 ], and environmental factors [ 10 , 11 ] have significant impact on POI development. In clinical applications, some interventions such as hormonal replacement therapy (using 17-β estradiol and dydrogesterone) [ 12 , 13 ] and traditional Chinese medicine [ 14 ] are intended to relieve endocrine disturbance or restore ovarian function; however, the effectiveness of these measures is limited. Recently, the therapeutic potential of stem cells in POI treatment has gained extensive attention due to their multipotent differentiation ability and diverse sources such as chorionic plate, adipose tissue, umbilical cord, bone marrow, skin and even menstrual blood [ 15 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic [ 7 , 8 ], immunological [ 9 ], and environmental factors [ 10 , 11 ] have significant impact on POI development. In clinical applications, some interventions such as hormonal replacement therapy (using 17-β estradiol and dydrogesterone) [ 12 , 13 ] and traditional Chinese medicine [ 14 ] are intended to relieve endocrine disturbance or restore ovarian function; however, the effectiveness of these measures is limited. Recently, the therapeutic potential of stem cells in POI treatment has gained extensive attention due to their multipotent differentiation ability and diverse sources such as chorionic plate, adipose tissue, umbilical cord, bone marrow, skin and even menstrual blood [ 15 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in traditional Persian medicine, the etiology of amenorrhea is divided into uterus etiology including the obstruction or blockage in the uterus due to dystemperament or inflammations, and the like, as well as common etiologies such as occasional dystemperament in the body or any disease in other organs which may disrupt mensuration (15,20,21). Several studies were found to use traditional and herbal methods to treat early menopause (2,(22)(23)(24) The patient of the current study reported having cold and dry dystemperament (suolmizaj) based on traditional medicine rules, which caused complaints about vaginal dryness, dyspareunia, obsessions thoughts, parasomnia, nightmare, the darkness of skin color, and dryness and itching of the skin. Digestive disorders of the patient were due to cold and dry dystemperament in the stomach leading to dyspepsia through which the elements fail to be properly absorbed and therefore are unable to reach the other parts properly.…”
Section: Discussionmentioning
confidence: 84%
“…However, the magnitude of such a decline varies in various countries (1). Early menopause and abnormal early infertility can affect self-efficacy and self-esteem (2). Premature ovarian failure (POF) is the disruption of the activity of ovaries before the age of forty.…”
Section: Introductionmentioning
confidence: 99%
“…For example, unexplained vaginal bleeding, a history of endometrial or ovarian neoplasm, acute liver injury, vascular embolization, breast cancer, poorly controlled diabetes, or hypertension are all contraindications of the treatment after menopause. [ 6 ] Therefore, prior to administration, risk assessment of HRT such as the presence of complications or existing medical conditions should be performed. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%